Knowledge Justice: An Opportunity for Counter-expertise in Security vs. Science Debates. (3rd July 2019) - Egert, Philip R.; Allen, Barbara L.
ABSTRACT: Knowledge justice provides a conceptual framework to apply principles of social justice in environments of competing interests regarding science. Both knowledge and its making can be seen as a good to be distributed, including all voices for whom the science will matter. In this framework, knowledge production is shared among a broader constituency of knowers representing both local and cosmopolitan voices. The problem of knowledge injustice can be seen in the U.S. government's recent attempt to secure scientific knowledge about H5N1 or avian bird flu virus. The censorship produced a global debate between scientists and policy-makers over how to balance the nation-state's desire for security with the life science's tradition of open and shared research. This conundrum, known as the dual-use dilemma, obscures larger questions that lie outside of expert-centered domains—namely the concerns of many communities in the Global South struggling with the impact of the virus in their daily lives. An example of such counter-expertise is that of the backyard poultry farmer whose ways of knowing are foreign to science and policy experts who frame the ways in which knowledge about H5N1 should be developed, controlled, and used. While the H5N1 debate illuminated competing positions regarding knowledge production between powerful elites, it ignored the social justice inequities produced by the dual-use dilemma. The concept of knowledge justice provides a way of thinking about science that can include locally situated counter-expertise, disrupting the dual-use dilemma produced by competing dominant priorities of security and public health.